Impact of mean platelet aggregation degree on long-term clinical outcomes among patients undergoing a complex percutaneous coronary intervention. Issue 6 (September 2017) - Li, Quan; Li, Mengmeng; Yu, Xianpeng; He, Jiqiang; Gao, Yuechun; Zhang, Xiaoling; Wu, Changyan; Luo, Yawei; Zhang, Yuchen; Ren, Xuejun
Abstract : Objective: The aim of this study was to evaluate the association between the mean platelet aggregation degree and long-term clinical outcomes in patients receiving a complex percutaneous coronary intervention (CPCI). Patients and methods: We screened 2141 patients after a percutaneous coronary intervention (PCI) treated with aspirin and clopidogrel. CPCI was defined as a procedure targeted to at least one of the following: left main disease, bifurcation lesion, ostial lesion, chronic total occlusion, and small-vessel stenting. ADP-induced platelet aggregation was serially measured by light transmission aggregometry at least three times after PCI and the mean value was calculated. The population was categorized on the basis of the mean ADP degree and the presence of CPCI. The primary endpoint measured was a major adverse cardiovascular and cerebral event (MACCE). Results: A total of 1245 patients enrolled in the study were divided into four groups: group A (CPCI and ADP≥40%), group B (CPCI and ADP<40%), group C (non-CPCI and ADP≥40%), and group D (non-CPCI and ADP<40%). The median follow-up was 29.9 months. The Cox multivariate analysis suggested that group A was an independent risk factor for MACCE (hazard ratio: 2.70, 95% confidence interval: 1.25–5.81; P <0.001). Compared with group A, the remaining groups (groups B, C, and D) had a lower rate of MACCE. When group C was set as the reference, groups B and D had similar risks for primary endpoints. Conclusion: Patients undergoing CPCI with a high mean ADP degree are at a high risk for MACCE. Serial platelet function testing is therefore important in patients receiving CPCI.